Experimental Investigation on Strength Characteristics of Light Weight Foamed Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
As part of this study, three distinct batches  of foamed concrete were produced: plain foamed concrete  (PFC), polypropylene fiber reinforced foamed concrete  (PPFC), and basalt fiber reinforced foamed concrete (BFC).  Compressive strength, splitting tensile strength, and, flexural  strength, were some of the tests that were performed on the  specimens. According to the findings of this research, using  the optimal foam volume, which was determined to be 20%,  results in a specific density of foam concrete that is between  342 Kg/m2and 490kg/m2and a compressive strength that  ranges from 20N/mm2to 38 N/mm2. Normal concrete was  combined with Styrofoam with an R-13 rating, normal  concrete was combined with PFC, normal concrete was  combined with PPFC, and normal concrete was combined  with BFC. When compared to the PFC specimen, the flexural  strength of the BFC specimen was 10 times greater. The BFC  beam specimen has shown the highest load bearing capability  of the RFC beam samples. In addition, the findings of the  experiments indicate that the combination of conventional  concrete and BFC has shown the maximum load bearing  ability when bent. The combination of standard concrete and  PFC has been demonstrated to have the maximum load  bearing capability among the compression columns.
Keywords: Plain foamed concrete (PFC); Polypropylene fiber reinforced foamed concrete (PPFC); and Basalt fiber reinforced foamed concrete (BFC); oamed concrete